Level of Heavy Metals and Pathogenic Bacteria in Tap Water of Rusafa side Hospitals in Baghdad - Khadem Zgair , Hameda (Diyala Journal of Medicine, 2022)
Background: The quality of drinking water supplied to hospitals is directly related to the quality of health services provided to people. Objective: To assess the chemical and microbial standards provided to four public hospitals on Baghdad's eastern side. Patients and Methods: In this study, 100 water samples were collected from water taps supplied to hospitals. Scientific methods were followed to collect samples in clean, sterile bottles. The chemophysical characteristics of the collected water samples were estimated (Hospital Imam Ali, Martyr Al-Sadr Hospital, Ibn Al Balady Maternity & Children's Hospital, Fatmih Alzahraa Maternity Hospital). In addition, the contamination of water with fecal-coliform bacteria was estimated. Results: In this study, 100 water samples were collected from water taps supplied to hospitals. Scientific methods were followed to collect samples in clean, sterile bottles. The chemophysical characteristics of the collected water samples were estimated (Hospital Imam Ali, Martyr Al-Sadr Hospital, Ibn Al Balady Maternity & Children's Hospital, Fatmih Alzahraa Maternity Hospital). In addition, the contamination of water with fecal-coliform bacteria was estimated. Conclusion: It can be concluded from the current study that the quality of water supplied to the hospitals covered by the study was within the standard level of physiochemical specifications. In addition, all samples were free of fecal-coliform bacteria, which indicates that the water supplied to the hospitals is not contaminated with feces.